EP250 Hysterectomy of closure after radiotherapy in cancers uterin collar at advance stages (retrospective study). (1st November 2019) - Assal, A; Maazar, D; Serraj, M; Benhessou, M; Ennachit, M; El Karroumi, M
Abstract : Introduction/Background: The standard treatment of locally advanced cervical cancer is the combination of a concurrent radiochemotherapy brachytherapy. The aime of this study was to evaluate the morbidity, also to determine the post therapeutic prognosis and its factors in disease free survival and overall survival at 2 years. Methodology: An observational retrospective monocentric cohort concerning 82 patients cared for cervical cancer stage IB2 between 2016–2017 was conducted. All patients included in this study were treated with radiochemotherapy brachytherapy followed by a completion surgery. Results: In this study, we had patients with epidermoide carcinoma in 93.90% and adenocaricnoma in 4.88%, with advanced stages, IIB (73.17%), IIIB (9.75%), IIA (12.19%), IB2 (1.22%) and IVA (1.22%). All patients recieved radiotherapy with 93.90% of patientes recieving between 41 and 50 Gy. 33 patients (40.24%) recieved a brachytherapy. 74 patientes (90.24%) recieved a chemotherapy (concomitant for 71 patients). The medium period of time between RCC and surgery was 12.5 weeks. The completion surgery was large (ACHE) in 75.61%, with a laparotomy in 63.41%. A lymphadenectomy was done at the same time in 75.61%. Peroperative difficulties were present in 6.10% of cases. Peroperative complications were observed in 16.63% (2.44% vascular lesion, 1.22% visceral lesion, 8.55% bleeding and 2.44% APO), no reanimation, surgical nor radiological treatment was required. None of the patients died in or after the surgery. Conclusion: Our study found a miner and acceptable rate of per and postoperative complications with no gravity. The analysis of complications risk factors and the prognosis factors suggest that the complete response rate, and higher rate of overall survival and disease free survival could be improved. Disclosure: Nothing to disclose.